Impact of nationwide lockdown on cancer care during COVID-19 pandemic: A retrospective analysis from western India. Issue 4 (July 2021) - Pareek, Ananya; Patel, Apurva A.; Harshavardhan, A.; Kuttikat, Philip G.; Pendse, Shantanu; Dhyani, Aruj; Sharma, Satish; Agarwal, Nikesh; Maji, Debajyoti; Reddy, Ramidi G.; Gupta, Yuganshu; Panchal, Harsha P.; et al.
Abstract: Background and aims: COVID-19 has impacted healthcare system worldwide including cancer case. Aim of this study was to describe the experience of lockdown on cancer care concerning patient's visit and reception of treatment in western India. Methods: This is a retrospective observational study conducted in patients with cancer attending a tertiary care center pre-lockdown and during lockdown (from January to May 2020). Data related to demographic parameters, type of tumor, type of treatment received and functional status of patients were retrieved from hospital medical records of patients. Results: Of the 5258 patients included, 4363 visited hospital pre-lockdown (median age, 50 years) and 895 visited during the lockdown period (median age, 47 years). A total of 1168 and 106 patients visiting hospital before and during lockdown, respectively, had comorbidities. Breast cancer (25.6% and 29.7%), head and neck cancer (21.3% and 16.9%) were the most common type of solid tumors; leukemia (58.0% and 73.0%), lymphoma (18.8% and 13.5%) and multiple myeloma (18.6% and 12.2%) were the most common type of hematological malignancies observed in patients visiting pre-lockdown and during lockdown, respectively. Chemotherapy was most commonly received treatment (pre-lockdown, 71.8%; during lockdown, 45.9%). Other therapies reported includes supportive/palliative, targeted, hormonal, and immunotherapy. The majority of patients who visited the hospital pre-lockdown (68.4%) and during lockdown (62.8%) had 0 or 1 Eastern Cooperative Oncology Group (ECOG) score. Conclusion: Overall observations highlight a substantial impact of an imposed nationwide lockdown during COVID-19 pandemic on cancer care of patients in terms of reduced patient visits and number of treatments received. Highlights: There may be challenges in the management of cancer during lockdown. This retrospective observational study evaluated such patients. Breast cancer was the most common solid cancer. Leukemia was the most common hematological cancer. A substantial impact on cancer care particularly with reduced patient visits.